Clinical case of gastroesophageal reflux disease of the fourth degree - Aleksandra V. Serezhkina; Irina G. Khmelevskaya; Natalya S. Razinkova; Irina I. Zhiznevskaya; Galina V. Shistilina; Elizaveta A. Romanova (LLC "MEDIAFORMAT", 2023)
Gastroesophageal reflux disease not only has a wide variety of clinical manifestations from the digestive system, but also affects other systems associated with it. due to the fact that this disease can occur under the mask of others, it is difficult to say how much it is widespread. due to the fourth degree of the disease, which is one of the most severe, the child needs the advice of a surgeon who will choose the tactics of further treatment and subsequent rehabilitation. Preventive measures for this pathology include: do not resort to tight swaddling, keep the baby in an upright position after feeding.